1998
DOI: 10.1109/50.664057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soliton interaction on timing jitter in communication systems

Abstract: Timing jitter in soliton communication systems is studied, taking into account both soliton interaction and amplifier noise. Deviations from Gordon-Haus jitter for closely spaced solitons are observed. A new analytical model for the timing jitter is proposed. The model presented considers interaction in a random sequence of solitons and the effect of the amplified spontaneous emission noise added in each amplification stage. We obtain a good agreement between the new analytical model and simulation results for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 11 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…It can be seen clearly that under the influence of SSFS, there is almost the same offset of two out-phase solitons to the dropping edge, which will result in the soliton separation will have no relation to SSFS effects. Recently, some papers report the effects of soliton interactions to timing jitter in soliton transmission systems [4]. We introduce the average standard deviation of timing jitter to evaluate the timing jitter in a soliton system by using the following equation: (b) (a) Fig.4 shows that under the influence of SSFS, the soliton interactions induced standard deviation of timing jitters of solitons.…”
Section: Impacts Of Ssfs To Fundamental Soliton Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen clearly that under the influence of SSFS, there is almost the same offset of two out-phase solitons to the dropping edge, which will result in the soliton separation will have no relation to SSFS effects. Recently, some papers report the effects of soliton interactions to timing jitter in soliton transmission systems [4]. We introduce the average standard deviation of timing jitter to evaluate the timing jitter in a soliton system by using the following equation: (b) (a) Fig.4 shows that under the influence of SSFS, the soliton interactions induced standard deviation of timing jitters of solitons.…”
Section: Impacts Of Ssfs To Fundamental Soliton Interactionsmentioning
confidence: 99%
“…Therefore, optical soliton communications have been widely applied in ultra high-speed long-haul optical communications, and in soliton communication systems, the transmission capacity could be improved using picosecond-subpicosecond solitons [1]. However, with the increase of bit rate, the time interval between two adjacent solitons decreases and the interactions between them play a major role in limiting the transmission distance [3,4]. Soliton interaction is a kind of pulling or pushing originated from optical nonlinearity, resulting in a significant reduction in the transmission capacity.…”
mentioning
confidence: 99%
“…2 We introduce the average standard deviation of timing jitter to evaluate the timing jitter in a PDM soliton system by using the following equation:…”
Section: Interactions Between Multiple Pdm Solitonsmentioning
confidence: 99%
“…1 But with increasing bit rate, the time interval between two adjacent solitons decreases and the interactions between them play a major role in limiting the transmission distance. 2,3 Experiments have demonstrated that the interaction between orthogonally polarized solitons is weaker than that of parallel-polarized solitons, and hence the polarizationdivision multiplexing ͑PDM͒ technique has been proposed to reduce the soliton interactions and increase transmission capacity by making adjacent solitons orthogonally polarized. 4 The soliton interactions in a PDM system have been analyzed theoretically using the variational perturbation method.…”
Section: Introductionmentioning
confidence: 99%
“…Optical fiber amplifiers have been playing an important role to compensate losses in WDM systems. Optical amplification adds noise to the signal which can lead to several detrimental effects [1][2][3]. Another major concern in high-speed optical communication systems is chromatic dispersion that can produce intersymbol interference [1,4].…”
Section: Introductionmentioning
confidence: 99%